A facile route to synthesize core/shell structured carbon/magnetic nanoparticles hybrid and their magnetic properties. (July 2015) - Qi, Xiaosi; Xu, Jianle; Zhong, Wei; Du, Youwei
Graphical abstract: Controllable synthesis of core/shell structured carbon/magnetic nanoparticles hybrid and their tunable magnetic properties. Highlights: The paper reports a simple route for core/shell structured carbon/magnetic nanoparticles hybrid. By controlling the temperature, Fe3 O4 @CNCs, Fe@HCNTs and Fe@LCNTs were produced selectively. The magnetic properties of the obtained core/shell structured hybrid could be tuned effectively. Abstract: By controlling the pyrolysis temperature, core/shell structured Fe3 O4 /carbon nanocages, Fe/helical carbon nanotubes and Fe/low helicity of carbon nanotubes could be synthesized selectively over Fe2 O3 nanotubes generated by a hydrothermal method. The transmission electron microscopic and scanning electron microscopic investigations revealed that the efficiency of generating core/shell structured hybrid was high, exceeding 90%. Because of the magnetic nanoparticles tightly wrapped in graphitic layers, the obtained core/shell structured hybrids showed high stability and good magnetic properties. And the magnetic properties of the obtained core/shell structured hybrid could be tuned by the decomposition temperature and time. Therefore, a simple, inexpensive and environment-benign route was proposed to produce magnetism-tunable core/shell structured hybrid in large quantities.